STRUKTUR KOMUNITAS TERIPANG (HOLOTHUROIDEA) DI BEBERAPA PERAIRAN PANTAI KAI BESAR, MALUKU TENGGARA - Yusron, Eddy; Widianwari, Pitra (Makara Journal of Science, 2004)
Holothurian (Holothuroidea) Community Structure in Some Coastal Waters of Kai Besar Island, South-East Maluku. During October and November 1990 the holothurian community inhabiting littoral areas was assessed at five locations : Borang, Ohoiwait, Nuwahan, Wahadan and Kurit Wur. This involved five ecological indices: density, species richness, diversity, evenness and similarity. It was revealed that the holothurian community consisted of 14 species in which five among them occurred in all locations at higher densities: Holothuria edulis, H. scabra, H. nobilis, H. atra and Stichopus chloronatus. Small variations of the ecological indices at all locations may indicate that the community characteristics at the five locations were relatively similar.